ANALISIS FENETIK KULTIVAR CABAI BESAR Capsicum annuum L. DAN CABAI KECIL Capsicum frutescens L. - Susi Agustina; Pudji Widodo; Hexa Apriliana Hidayah (Scripta Biologica, 2014)
A study on the “Phenetic analysis of Capsicum annuum L. and Capsicum frutescens L. “ has been conducted from June to August 2012. The aim of the research is to know the relationship amoung big chillis and small chillis based on morphology. The samples were taken from 5 villages in Sukamantri Sub-district, Ciamis. The method used in this research was explorative survey with purposive random sampling. The character data of big chili and small chili morphologies were analyzed descriptively to determine the relationship using UPGMA (Unweighted Pair Group Mean Arithmetic) methods. The result of this study showed that there were seven cultivars of big chilli, namely C. annuum „Hot Chili‟, Gada, Fantastik, Keriting TM 888, Tanjung 2, Keriting TM 999, Hot Beauty, and four cultivars of small chilli namely C. frutescens „Cakra Ungu‟, Cakra Hijau, Bendot, and Cakra Putih. The fenogram showed that there were five groups, two groups of C. annuum and three groups of C. frutescens. The first group consisted of C. annuum „Hot Chili‟, Keriting TM 888, Fantastik, and Tanjung 2. The second group consisted of C. annuum „Gada‟, Hot Beauty, and Keriting TM 999. The third group was C. frutescens „Bendot‟. The fourth group consisted of C. frutescens „Cakra Putih‟, and C. frutescens „Cakra Hijau‟. The fifth group was C. frutescens „Ungu‟. The closest relationship was between C. annuum „Keriting TM 999‟ and C. annuum „Hot Beauty‟ and the farthest relationship was between C. frutescens „Bendot‟ and C. frutescens „Ungu‟.